Spreading of antibiotic resistance as a result of soil fertilization by manure composts containing oxytetracycline and antibiotic-resistant genes - N.V. Danilova; P.A. Kuryntseva; M.Sh. Tagirov; P.Yu. Galitskaya; S.Yu. Selivanovskaya (Учёные записки Казанского университета: Серия Естественные науки)
Due to the active usage of antibacterial drugs in animal husbandry, antibiotic residues and antibiotic-resistance genes enter the soil when it is fertilized with manure and compost. In this work, we estimated the spread of antibiotic-resistance genes in the soil when it was fertilized with composts containing oxytetracycline (OTC) and tetracycline-resistance genes. The following mixtures were studied for 35 days: the soil with “clean” compost, the soil with compost and 300 mg kg–1 OTC, the soil with compost and antibiotic-resistance genes. In the soil treated with composts, the number of bacteria and fungi increased, with the greatest changes in the number of bacteria observed for the soil with compost containing OTC. The addition of compost with the antibiotic and the resistance genes tet(M) and tet(X) to the soil led to the formation of antibiotic resistance in soil microorganisms with the highest number of gene copies for 5–7 days: an average of 3.31?106 and 7.77?106 copies g-1, respectively. Both genes, tet(M) and tet(X), but in smaller numbers, were detected in the soil with “clean” compost on days 14–21, respectively.